APRESIASI TERHADAP BATIK SISWA SEKOLAH MENENGAH KEJURUAN - Reni Susi Subekti (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2019)
The purpose of this study was toÂ describe appreciation of batik. This study included the type of ex-post facto research. Data collection method used questionnaire and documentation. Data analysis techniques used descriptive analysis techniques to find the average value, standard deviation, mean, median, and mode. The results showed that the perception of batik was in a high category with a relative frequency of 75.86%. Data on students' perceptions of batik has four indicators, namely the level of fondness, enjoyment, reaction, and productivity. Frequency distribution and indicator categories are explained as follows. (1) The level of interest in batik in the high category. (2) Enjoy levels of batik. (3) Levels of reacting to batik in sufficient categories. (4) Productive levels of batik in sufficient categories.